ISLAM AND LOCAL CULTURE : The Tense between Problem of Approach and Local Wisdom of Javanese Community - Abu Hapsin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Local wisdom is the result of a process of dialogue between universality, Islam and local culture. In this case, Islam is presented in its substantive form, and the container (form) can use the social system applicable to the local community. This is what inclusive Islam means, that is, Islam is open to assimilating different elements of (foreign) cultures outside of Islam and then making them part of the Islamic tradition. In order to avoid syncretism, in the process of cultural assimilation, of course, the substantive elements must first be sorted out from the formal elements